Copper Removal from Synthetic Water by Using Rice Husk Activated Carbon - Malik, Alia Farhana; Hamidon, Nuramidah (Journal of Advanced Industrial Technology and Application, 2021)
One of the most efficient ways of replacing the existing traditional technique is the application of low-cost adsorbent. Rice husk (RH) is an abundant and inexpensive material and can be processed for various applications into activated carbon (AC). In the past couple of years, AC has also been used as an adsorbent. In addition, AC has wider used, such as removing water and wastewater from different contaminants. In this analysis, the raw rice husk for removing copper from synthetic water is treated and modified as activated carbon for copper (II). Using alkaline sodium hydroxide solution, NaOH, which has a different adsorbent dosage, rice husk was prepared. The parameters to be tested before and after the absorption process are pH, turbidity, total suspended solid, and dissolved oxygen (DO) of the synthetic water. The result obtained indicates that different dosages of adsorbent have different effects on the consistency of the water. The adsorbent dose used was 0.6g, 1.6g, 2.6g, 3.6g, and 4.6g, respectively. In short, an effort has been made on using rice husk as an adsorbent, as the major parts of the adsorbent were lignin and silica, which encouraged the adsorption process. Based on the previous rice husk activated carbon results, this has been verified that the activated carbon intensity will extract copper from the water sample.